The sustainability of financial innovation in e-payment systems - Jain, Deepa; Dash, Manoj Kumar; Thakur, K. S. (Emerald Publishing Limited, 2023)
The financial system is the heart of an economy and payment systems are the nerves. As we shift towards a cashless economy, it is essential to understand the perception of customers towards digital transactions to design effective and viable E-Payment Systems (EPSs). Drawing on ten years of research in India and around the world, The Sustainability of Financial Innovation in E-Payment Systems presents a timely and important model for the long-term viability of EPSs and gives real-world strategies for creating a positive, tangible economic impact. Academics, policy makers, commercial decision-makers, and researchers will find this volume indispensable as they seek to maximise the positive impacts of todays rapid, ongoing changes.